Satisfaction with the oral health services. A qualitative study among non-commissioned officers in the Malaysian armed forces - Esa, R.; Rajah, P.; Razak, I.A. (2006)
Patient satisfaction is critical for the growth and prosperity of any oral health service or practice. The success of any oral health service can be assessed by an evaluation of the degree of satisfaction/dissatisfaction of its patients. Objective The aim of this study is to assess satisfaction/dissatisfaction with the oral health services among Non-Commissioned Officers (NCOs) in the Malaysian Armed Forces (MAF). Method A qualitative study using the Nominal Group Technique was undertaken. Eighty subjects from the Rasah Camp, Seremban were randomly selected from four lists, namely privates, male and female corporals and sergeants and were Grouped into 10 discussion groups of eight participants each. Of the 10 groups, four groups comprised male corporals.. three groups of privates, two groups of sergeants and one group of female corporals. Two separate discussion sessions were conducted to elicit factors/items causing dissatisfaction and satisfaction expressed by the participants. Every participant then scored all the factors perceived as important by members of the group. The score ranged from 0-9 i.e., the least to the most important. Scores were weighted, and the weighted score of every participant for each item was added. The ratings of the factors were determined by comparing the sum Of the weighted scores. Results The six most important factors/items rated in the satisfaction discussion were modern equipment (9.07), friendly dentist (8.27), pleasant surgery (8.23), good quality treatment (7.93), friendly staff (7.18) and pain alleviation (6.07). These factors were further regrouped into three broad categories i.e. (1) Clinic set-Lip, (2) Patient-personnel interaction (PPI) and (3) Technical competency (TC). In the dissatisfaction discussion six factors/items were rated i.e. long waiting time (10.39), sequence of treatment not followed (7.18), non-availability of dentist (7.16), unfriendly staff (7.05), poor quality treatment (6.80) and restricted time for treatment (5.98). The three most important categories in the dissatisfaction discussion were (1) Administrative efficiency, (2) PPI and (3) TC. Conclusion A conceptual model was developed to explain the factors affecting patients' satisfaction/dissatisfaction with the oral health services. It is recommended that a questionnaire Survey be undertaken to validate and reflect the entire population of the MAF. Remedial measures highlighted in the areas of dissatisfaction should be addressed accordingly based on the quantitative study.